SIFAT BALOK KOMPOSIT KOMBINASI BAMBU DAN KAYU - Abdurachman; Nurwati Hadjib; Jasni; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 2015)
Combination of bamboo and wood composite beam is one possible laminated product to be developed. Generally, the composite product of solid wood meet the strength requirement for construction. However, composite beam combination of bamboo and wood has not been studied intensively. This paper observes the properties of composite combination of three bamboo species: andong, petung and ori with jabon wood species using isocyanate glue and merbau extracts. In order to improve composite’s durability, bamboo and jabon wood were preserved using 7% of boric acid and borax. Result shows composite beam combination of bamboo and jabon wood bonded with isocyanate is found to be the best composition in term of physical and mechanical properties. The density of the composite beam is 0.64 g/cm³ in 9.70% moisture content. Modulus of Elasticity (MOE) 78,168 kg/cm², Modulus of Rupture (MOR) 384 kg/cm² and compression parallel to the glue line is 378 kg/cm².